Decision Support System for The Selection of Achieving Student Using Analytical Hierarchy Process Method - Yulanda Yunus; Ona Maliki (STMIK Budi Darma, 2021)
This study designed the Selection of Outstanding Students. To produce new findings in the world of technology, a lot of research has been carried out, especially for the world of education. One example is the selection of outstanding students where, this selection is needed by the school for external purposes, such as providing data on outstanding students to the Education Office, providing scholarships to students who excel, and making it easier for schools to enter every student in competitions in the world of education. The purpose of the research is that this selection system for high achieving students can be used by schools that want to select outstanding students, for example speed and accuracy in determining outstanding students. Because if this selection is done by someone, it will still experience inaccuracies or it could be subjective. The method used in this research is the Research and Development method or known as the research and development method. This research method is defined as a research method used in producing certain products and testing the effectiveness of these products, testing the system using the test case method with a white box testing and black box testing approach. The Analytical Hierarchy Process (AHP) method can help the process of determining outstanding students, based on trials using white box and black box testing resulting in a Ciclometic Complexity (CC) = 3, said to be appropriate and feasible to use and implement.